Komunitas dan Preferensi Habitat Gastropoda pada Kedalaman Berbeda di Zona Litoral Danau Singkarak Provinsi Sumatera Barat - Yuli Wendri; Jabang Nurdin; Indra Junaidi Zakaria (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2019)
This research was conducted in Lake Singkarak from February to March 2016, using purposive sampling method in three locations namely Tanjung Mutiara, Malalo and Paninggahan, at a depth of 0.5 m, 1 m and 1.5 m in each location. Samples were collected using 30x30 cm2 surber net. The result showed four gastropod species from family of Thiaridae, namely Melanoides granifera, Melanoides tuberculata, Brotia costula and Thiara scabra. Average population density of gastropod in Lake Singkarak was 399.75 ind / m2. The population density at depths ranging from 271.11 to 568.89 ind/m2, the highest population density is showed at a depth of 1.5 m and the lowest at a depth of 0.5 m. Melanoides tuberculata shows highest density at all depths. M. granifera prefers habitats with a depth of 1.5 m, M. tuberculata prefers a depth of 1 m, T. scabra prefers a depth up to 1.5 m and B. Costula prefer habitat with a depth of 0.5 m. Condition of Lake Singkarak shows as favorable and suitable habitat for gastropod’s life.